2021
DOI: 10.3390/antiox10030450
|View full text |Cite
|
Sign up to set email alerts
|

A Novel ALDH2 Activator AD-9308 Improves Diastolic and Systolic Myocardial Functions in Streptozotocin-Induced Diabetic Mice

Abstract: Diabetes mellitus has reached epidemic proportion worldwide. One of the diabetic complications is cardiomyopathy, characterized by early left ventricular (LV) diastolic dysfunction, followed by development of systolic dysfunction and ventricular dilation at a late stage. The pathogenesis is multifactorial, and there is no effective treatment yet. In recent years, 4-hydroxy-2-nonenal (4-HNE), a toxic aldehyde generated from lipid peroxidation, is implicated in the pathogenesis of cardiovascular diseases. Its hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 81 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Coherent to the previous studies, we demonstrated that the triggering of autophagy was involved in PASMC migration and proliferation. ALDH2 was reported to attenuate cardiovascular diseases through the regulation of autophagy including heart failure [ 16 ], diabetic cardiomyopathy [ 51 ], and myocardial dysfunction [ 52 ]. However, most studies emphasized on the direct detoxification properties of ALDH2 instead of its interactions with autophagy, especially in the scenario of PH.…”
Section: Discussionmentioning
confidence: 99%
“…Coherent to the previous studies, we demonstrated that the triggering of autophagy was involved in PASMC migration and proliferation. ALDH2 was reported to attenuate cardiovascular diseases through the regulation of autophagy including heart failure [ 16 ], diabetic cardiomyopathy [ 51 ], and myocardial dysfunction [ 52 ]. However, most studies emphasized on the direct detoxification properties of ALDH2 instead of its interactions with autophagy, especially in the scenario of PH.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated reductions in the expression level and enzymatic activity of ALDH2 in diabetic hearts. The ALDH2 activator AD-9308 improved cardiac diastolic and wall remodeling in diabetic mice [ 81 ].…”
Section: Molecular Mechanism Of Diabetic Cardiomyopathymentioning
confidence: 99%
“…AD-9308 is a highly selective ALDH2 activator that is more potent than the prototype drug Alda-1. We previously demonstrated that AD-9308 ameliorated diabetic cardiomyopathy through the restoration of ALDH2 activity and by reducing the 4-HNE level [ 81 ]. In this study, AD-9308 ameliorated myocardial fibrosis, inflammation, and apoptosis; improved mitochondrial respiration and calcium handling; reduced autophagy in cardiac tissues; and reversed myocardial remodeling and dysfunction in streptozotocin-induced diabetic mice.…”
Section: Emerging Treatment Targeting Specific Mechanisms Of Diabetic...mentioning
confidence: 99%
“…Owing to the increasing scope of ALDH2*2 association with disease, significant interest and research effort have been devoted to targeting ALDH2 in disease prevention and treatment ( Gao et al, 2022 ; Zhang and Fu, 2021 ; Kimura et al, 2019 ; Chen et al, 2014 ; Lee et al, 2021 ). Small-molecule ALDH2 enzyme activators, such as Alda-1 and Alda-64, that can enhance the wild-type ALDH2 activity and restore the structure and function of the ALDH2*2 variant enzyme have been reported and, if effective in humans, could reduce the risk of developing associated disease ( Chen et al, 2008 ; Perez-Miller et al, 2010 ; Chen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%